KAJIAN BIAYA PRODUKSI, HARGA POKOK DAN BATAS KEUNTUNGAN PADA PENGOLAHAN PRODUK BERSAMA PENGERJAAN KAYU - Setiasih lrawati; l M Sulastiningsih; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The study on production cost, base price and profit margin was conducted in wood working industry using sawn timber of perupuk (Lophopetalum spp.), meranti (Shorea spp.), damar (Agathis spp.) and jangkang (Xylopia spp.) for various joint products. The products were moulding, S4S. Solid jointed board, finger jointed board, finger jointed stick and door jamb. There were five products of perupuk, two of meranti, two of'jangkang and one of damar.The results of tire study showed that the method of joint cost calculation used by the mill was average cost per unit method. Production costs of jangkang and damar wood working products were higher than those of meranti and perupuk. The average proponion of raw materials, wages and others on the total production cost was respectively 62%, 4/% and 34%. Proportion of wage cost was small, on the contrary, proportion of other production cost was relatively high. Among ten kinds of wood working joint products, only three yielded a positive profit margin, namely, moulding, S4S and finger jointed board of perupuk.Based on the average cost per unit method the raw material cost, production cost and base price of S4S were lower than those of finger jointed stick. This results was irrational since the raw material cost of S4S should be more expensive than that of finger jointed stick. Consequently, the average cost per unit method was not suitable for joint cost distributing method of wood working joint products. Therefore. it is suggested for replacing this method with one that considers quality and price of raw material and the product selling price.